Drift, Capture, Break, and Vanish: Sea Ice in the Soviet Museum of the Arctic in the 1930s - Lajus, J.; Maclennan, R. (2022)
In the 1930s, Arctic sea ice became very visible in Soviet life. Moving sea ice was recognized as an important actant in polar expeditions of different kinds: the Chelyuskin disaster, the icebreaker Krasin rescue voyage, Papanin’s drifting research station on an ice floe. Sea ice gradually stopped being seen as an obstacle in political and cultural discourses and became an element in the process of environing –transformation of nature into environment. To facilitate this process, however, sea ice needed to be carefully studied to better understand and predict its movements. Wherever possible the ice should become friendly, along with the rest of the Arctic that was also becoming friendly, as its most dangerous features were overcome thanks to human-induced transformation. This chapter considers the spaces and collections of the Museum of the Arctic, which opened in 1937 in Leningrad, with the focus on how sea ice was reimagined, depicted, and engaged with. It demonstrates how attitudes towards sea ice, and the ways of representing it that were established in the 1930s, continue to exert a powerful influence today. Icebreakers remain important objects and protagonists in the transformation of Arctic sea ice and continue to exert power as both heroic heritage and powerful contemporary symbols of Russian Arctic development and dominance.